Crunchy Bitez / Dayang Rohana Awang Hamit ... [et al.] - Awang Hamit, Dayang Rohana; Galawis, Felesia; Alih, Dumil; Mohd Zawawi, Siti Noorhayati; Alphonsus, Emylie (2009)
Nowadays, there are many forms of businesses exist in Malaysia especially in Sabah. Normally, the entrepreneurs involved in the business of products or services. However, it totally depends to entrepreneurs to decide what types of business they want to involve in. Normally, the main agenda of entrepreneurs get involve in business is to gain as much profit as he can. To do so, entrepreneurs must then need to identify and use all the available opportunities. Bread is one of the most favorite meals taken not only during breakfast but also during leisure time and workdays as well. Having bread as breakfast meals is a best way to provide enough energy to our body for the whole day. Furthermore if we have no time to prepare other breakfast meal such as fried noodle or Nasi Lemak especially for working people. Ordinary bread unable to sustain in a good condition as its expiration date will only be around 4 to 5 days after delivered to the shops or bakery. Thinking of this problem, that is why we would like to proposed our product Crunchy Bitez, flavored "Roti Bakar" that will meet customer or respectively those bread-lover satisfaction whereby they may enjoy having flavored and ready baked bread during breakfast, working period or even leisure time. The most interesting part is where they could keep Crunchy Bitez bread up to 3 weeks. Crunchy Bitez bread produced from expired bread, and comes with 4 most wanted and popular flavor, which are blueberry, strawberry, apricot, and orange. "Easy, Fast, Absolutely Delicious" stands for our promises to provide the most easiest and fastest way to enjoy absolutely delicious Roti Bakar, not only for breakfast but also at any time. We definitely realize that it is tough enough to compete with other well-established bread product, but we take these challenges as a gold opportunity to be succeeded and sustain in food industry.